Investigation into the Distribution Characteristics and Sources of Dissolved Gases in the Offshore Waters of Dingzi Bay, South Yellow Sea - Jingtao Zhao; Xuebo Yin; Kaixin Yu; Zhenfei He; Kuiying Zhang; Fuyu Wu; Jing Kan; Libo Wang; Hao Tian; Yong Zhang (Journal of Marine Science and Engineering, 2026)
Utilizing seawater samples collected during the summer of 2025 in the Dingzi Bay region, South Yellow Sea, this study conducted a comprehensive analysis of the contents and concentrations of dissolved gases (N2, O2, Ar, CO2) and hydrocarbon gases (such as methane, ethane, and propane). The findings reveal that the dissolved gases in the study area are predominantly composed of N2 and O2, with average proportions of 77.8% and 21.6%, respectively. Notably, significant CO2 anomalies were detected at certain stations, which may indicate intense organic matter degradation or the introduction of external fluids. Furthermore, wet gas constituents, including propane, butane, and isobutane, were identified in several samples, suggesting potential submarine oil and gas seepage or subsurface thermogenic gas input. Spatial analysis revealed that anomalous points were primarily concentrated at stations CJ01, CJ08, CJ10, and CQ01, with no significant correlation to water depth, suggesting that their distribution may be influenced by local geological structures or bottom currents. This study elucidates the complexity and heterogeneity of dissolved gas composition in the waters of Dingzi Bay, thereby providing a novel scientific foundation for regional carbon cycle research, seabed resource exploration, and marine environmental monitoring.